2022
DOI: 10.3390/curroncol29070376
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Patient-Reported Outcome Measure for Moist Desquamation among Breast Radiotherapy Patients

Abstract: There has been an increasing interest in patient-reported outcome (PRO) measures in both the clinical and research settings to improve the quality of life among patients and to identify when clinical intervention may be needed. The primary purpose of this prospective study was to validate an acute breast skin toxicity PRO measure across a broad sample of patient body types undergoing radiation therapy. Between August 2018 and September 2019, 134 women undergoing adjuvant breast radiotherapy (RT) consented to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In previous studies, clinicianrated and patient-reported measures of moist desquamation are associated with reasonably high levels of agreement, indicating this dichotomous endpoint could be assessed either by objective clinician examination or patient report. 51,52 Since the development of moist desquamation is such a clinically meaningful event for patients, outcome measures focused on the cumulative incidence of moist desquamation rather than CTCAE grade 2 þ RD (which includes patchy moist desquamation, moderate/brisk erythema or moderate oedema) may more reliably identify topical agents with clinical benefit. 27 This study was not powered to detect a difference in the cumulative incidence of RD between groups, so the findings regarding RD should be interpreted with caution.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…In previous studies, clinicianrated and patient-reported measures of moist desquamation are associated with reasonably high levels of agreement, indicating this dichotomous endpoint could be assessed either by objective clinician examination or patient report. 51,52 Since the development of moist desquamation is such a clinically meaningful event for patients, outcome measures focused on the cumulative incidence of moist desquamation rather than CTCAE grade 2 þ RD (which includes patchy moist desquamation, moderate/brisk erythema or moderate oedema) may more reliably identify topical agents with clinical benefit. 27 This study was not powered to detect a difference in the cumulative incidence of RD between groups, so the findings regarding RD should be interpreted with caution.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…A previously validated patient-reported outcome (PRO) questionnaire was completed by patients at similar timepoints as the staff skin assessments. 20 Patients were asked to report on whether they developed open skin in the fold under the breast. This included the inferior surface of the breast, the breast crease, and the chest wall below the breast when an inframammary breast fold was present.…”
Section: Methodsmentioning
confidence: 99%